Quadratic gravity theories in 2+1 dimensions and the topological Chern-Simons term - Accioly, Antonio [UNESP] (American Physical Society (APS), 2003)
The addition of a topological Chern-Simons term to three-dimensional higher-derivative gravity is not a good therapy to cure the nonunitarity of the aforementioned theory. Moreover, [Formula Presented] gravity in (2+1)D, which is unitary at the tree level, becomes tree-level nonunitary when it is augmented by the abovementioned topological term. Therefore, unlike what is claimed in the literature, topological higher-derivative gravity in (2+1)D is not tree-level unitary and neither is topological three-dimensional [Formula Presented] gravity. © 2003 The American Physical Society.